Thermoluminescence and optically stimulated luminescence measured in marine sediments indicate precipitation changes over Northeastern Brazil - Mendes, Vinícius R.; Sawakuchi, André O.; Chiessie, Cristiano M.; Giannini, Paulo C. F.; Rehfeld, Kira (Paleoceanography and paleoclimatology, 2019)
Marine sediment cores offer a great number of proxies for reconstructions of past environmental conditions, such as ocean temperature, salinity, primary productivity, stratification of the upper water column, and continental precipitation. Up to date, continental precipitation archived in marine sediment cores is reconstructed based mainly on the hydrogen isotopic composition of plant-wax compounds (i.e., n-alkane δD) or on the ratio between terrigenous and marine sediments expressed as elemental ratios (e.g., ln (Fe/Ca)). Although these proxies provide reliable precipitation reconstructions, there are some inherent limitations, as plant-wax δD application depends on the availability of n-alkanes in marine sediments and elemental ratios can be influenced by other factors like the relative sea-level, primary productivity, and postdepositional processes. Here we introduce new precipitation proxies based on optically stimulated luminescence and thermoluminescence signals of quartz and feldspar. The rationale is that when precipitation changes over the catchment through time, different sediment sources regarding weathering intensity and parent rock types are drained, supplying sediments with varying signals of luminescence to the ocean. We compared our new proxy records with records of well-established proxies, for the same (ln (Fe/Ca)) and neighboring (n-alkane δD) marine sediment cores. The comparison among all proxies as well as with a state-of-art transient climate model run (TraCE-21ka) demonstrates that the new proxies accurately constrain precipitation changes over northeastern Brazil for the last 30,000 years. The main advantage of these new proxies relies on their fast response to precipitation changes over the continent. Furthermore, they are straightforward to measure and not expensive.